NILAI-NILAI PENDIDIKAN AKHLAK PADA KISAH NABI MUSA DAN NABI KHIDIR DALAM AL-QUR’AN - Mufti Umma Rosyidah; Fathurrahman Alfa; Mutiara Sari Dewi (VICRATINA, 2020)
Islamic education is education that is based on the teachings of the Islamic religion. Because, the teachings of Islam rely directly on the Qur'an, As-Sunnah (hadith), the opinions of the Ulama '(Ijma'), Qiyas, and historical heritage. Islamic education has the same essential values and meanings as moral education and moral education values. The morals of Islamic students have now begun to be eroded, the Qur'an and Sunnah have also begun to be ignored, meanwhile these guidelines are the primary elements in the formation of morals. The morals of Islamic students in Indonesia began to decline due to several factors. Among them are: guidelines for faith in religion have begun to be pressured; the effectiveness of moral development in the family, school and in the community is still lacking; one's desire to follow western cultural trends which are materialistic, hedonistic and secularistic; lack of religious and moral education, and so on. The background of the above research is about educational values in the story of Prophet Moses  and the Prophet Khidr in QS. Al-Kahf verses 60-82. The purpose of this study is to describe the educational values in the story of the Prophet Moses and the Prophet Khidr in QS. Al-Kahfi verses 60-82. To achieve the above research objectives, the study was conducted with the type of library research. In this study, researchers interpreted the educational values of the story of the Prophet Musa and the Prophet Khidir in the QS. Al-Kahfi verses 60-82. educational values among others are tawadhu value, the value of patience, trust value, the value of discipline, meek value, the value of being serious in learning, the ethical value of the teacher towards students, the ethical value of students towards the teacher and I'tiqadiyah values (have faith in the provision of God).